Pembentukan Galur Haploid Ganda Padi Gogo dengan Sifat-Sifat Tipe Baru melalui Kultur Antera - Reny Herawati; Bambang S. Purwoko; Nurul Khumaida; Iswari S. Dewi; Buang Abdullah (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2008)
The breeding of upland rice with New Plant Type characters in relatively short time can be done by using anther culture technique. The technique has been recognized as a rapid and efficient technology for crop improvement. Plant materials used in this research were F1 crossing P1 (Fatmawati x Way Rarem), P2 (Fatmawati x SGJT-28),  P3 (Fatmawati x SGJT-36), P4  (Way Rarem x Fatmawati), P5 (SGJT-28 x Fatmawati), and P6  (SGJT-36 x Fatmawati). Media for calli induction (N6) and regeneration (MS) were according to Dewi methods (2003). The results of this study indicated that P3 (Fatmawati x SGJT-36) and P6 (SGJT-36 x Fatmawati)  from resiprocal crosses gave better response in anther culture than the others crosses for their calli induction and green plant regeneration. From the six F1 crosses, 348 (53.5%) spontaneous doubled haploid (DH) pure lines were obtained, six lines from Farmawati x Way Rarem, 13 lines from Fatmawati x SGJT-28, 187 lines from Fatmawati x SGJT-36, three lines from Way Rarem x Fatmawati, five lines from SGJT-28 x Fatmawati, and 134 lines from SGJT-36 x Fatmawati.  These lines should be evaluated and characterized for their agronomical and morphological  traits.    Key words: Anther culture, doubled haploid, callus induction, green plant regeneration